2022
DOI: 10.3390/nu14112269
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Environmental Exposure to Persistent Organic Pollutants and Indices of Overweight and Cardiovascular Risk in Dutch Adolescents

Abstract: Persistent organic pollutants (POPs) may have obesogenic effects. Knowledge about the effects of prenatal exposure to POPs on anthropometric measurements and metabolic parameters into adolescence is limited. Therefore, the aim of the current study was to determine whether prenatal environmental exposure to several POPs is associated with indices of overweight and cardiovascular risk in 13–15-year-old children. In this Dutch observational cohort study, 194 mother–infant pairs were included (1998–2002). Maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…BWQS regressions were stratified by sex due to potential sex-specific effects of some EDCs. [35][36][37] We note that sex interactions were not tested due to the absence of interaction testing functions in the BWQS package. Sensitivity analyses to ensure results robustness included (1) single-exposure analyses using linear regressions, correcting for multiple testing with false discovery rate (FDR) and assessment of between-cohort heterogeneity using the I 2 statistic of association 38 ; (2) mixture analyses for lipophilic compounds, stratifying mothers by gestational weight gain according to the Institute of Medicine guidelines 39 ; (3) phthalate mixture analysis, incorporating molar sums of DEHP and DiNP metabolites; (4) metal and persistent mixture analysis, including sum of PCBs, and nonpersistent mixture analysis, incorporating molar sums of DEHP, DiNP, and parabens; and (5) testing main significant mixture associations with a binarized MetS risk outcome, using the 80th percentile as the cutoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BWQS regressions were stratified by sex due to potential sex-specific effects of some EDCs. [35][36][37] We note that sex interactions were not tested due to the absence of interaction testing functions in the BWQS package. Sensitivity analyses to ensure results robustness included (1) single-exposure analyses using linear regressions, correcting for multiple testing with false discovery rate (FDR) and assessment of between-cohort heterogeneity using the I 2 statistic of association 38 ; (2) mixture analyses for lipophilic compounds, stratifying mothers by gestational weight gain according to the Institute of Medicine guidelines 39 ; (3) phthalate mixture analysis, incorporating molar sums of DEHP and DiNP metabolites; (4) metal and persistent mixture analysis, including sum of PCBs, and nonpersistent mixture analysis, incorporating molar sums of DEHP, DiNP, and parabens; and (5) testing main significant mixture associations with a binarized MetS risk outcome, using the 80th percentile as the cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…BWQS characteristics are available in eAppendix 2 in Supplement 1. BWQS regressions were stratified by sex due to potential sex-specific effects of some EDCs . We note that sex interactions were not tested due to the absence of interaction testing functions in the BWQS package.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the discovery that PCBs can undergo hydroxylation through natural and anthropogenic means to form hydroxylated polychlorinated biphenyls (OH‐PCBs) has raised serious environmental concern because OH‐PCBs are known to be several orders of magnitude more toxic than the parent PCBs (Tehrani & Van Aken, 2014). Previous studies have shown that exposure of humans and animals to OH‐PCBs causes certain biological perturbations that are linked to the following downstream events and adverse outcomes: disruption of thyroid homeostasis, breast cancer, prolonged estrous cycle, decreased mental development index, low birth weight, alteration in steroid homeostasis, increased incidences of cervicovaginal track tumor, and increased levels of cardiometabolic risk factors (Berghuis et al, 2022; Dirinck et al, 2016; Kezios et al, 2017; Martinez et al, 2005; Meerts et al, 2004; Nomiyama et al, 2010; Park et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether lower birth weight and lower thyroid levels are related to the development of overweight and obesity is unclear. In this Special Issue, Berghuis et al showed that higher levels of the contaminants, PCB, OH-PCB and PBDEs, in mothers were associated with metabolic cardiovascular risk markers for developing obesity and cardiovascular diseases in their offspring when measured during adolescence, especially in boys [8].…”
mentioning
confidence: 99%